Construction of a heat-resistant strain of Lentinus edodes by fungal Hsp20 protein overexpression and genetic transformation - Ling, Yun-Yan; Ling, Zhi-Lin; Zhao, Rui-Lin (Frontiers in Microbiology, 2022)
The shiitake mushroom (Lentinus edodes) is the second most popular edible mushroom globally due to its rich nutritional value and health benefits associated with consumption. However, the characteristics of growing at low temperatures limit the area and time of its cultivating. We selected a low-temperature cultivar as the original strain. We proposed to construct a heat-shock protein expression vector to achieve genetic transformation in this low-temperature strain to improve the survivability of the strain against the heat-shock response. To construct a heat-tolerant strain using the homologous recombination method, the L. edodes gpd promoter and the Agaricus bisporus heat-shock protein hsp20 gene were cloned and the expression vector pEHg-gdp-hsp20 was constructed. The two CaMV 35S promoters in the pCAMBIA1302 vector were then replaced with the gpd promoter to initiate the hygb marker and the mgfp5 reporter gene sequentially. Finally, the hsp20 gene carrying the gpd promoter was inserted into the vector to complete the construction of the expression vector pEHg-gdp-hsp20. This vector was transferred into dikaryotic and monokaryotic mycelia by the Agrobacterium tumefaciens-method. The integration of hygb and hsp20 into the genome of L. edodes mycelia by the gpd promoter was verified by growth experiments on resistant plates and PCR analysis. Expression of the reporter gene mgfp5 was verified by fluorescence microscopy analysis, which resulted in a positive statistical rate of 18.52% and 26.39% for dikaryon, and monokaryon, respectively. Real-time PCR analysis showed that the expression of the hsp20 gene was more than 10-fold up-regulated in the three transformants; the mycelia of the three overexpression transformants could resume growth after 24h heat treatment at 40℃, but the mycelia of the starting strain L087 could not recover growth at 25℃ indicating that strains that successfully expressed hsp20 had greater overall recovery after heat shock.